THE EFFECT OF SOCIAL MEDIA MARKETING ACTIVITIES ON BRAND EQUITY IN THE E-COMMERCE INDUSTRY IN INDONESIA - Linda Waty; Sri Vandayuli Riorini; Fadhil Rezky Ananda (Journal of Social and Economics Research, 2026)
This study examines the impact of Social Media Marketing Activities (SMMA) on consumer-based brand equity (CBBE) in the e-commerce industry in Indonesia. This topic is interesting because SMMA increases brand awareness and brand image for skincare products through creative content (Murdjaya & Faisal, 2025), and Shopee Live's strategy influences purchasing decisions for The Originote (Fernando et al., 2023). The main issue is how SMMA affects CBBE elements (brand awareness, perceived quality, brand association, brand loyalty) in Indonesian e-commerce. Research question: Does SMMA significantly influence CBBE in the Indonesian e-commerce industry? This study fills a gap because previous studies have focused more on customer satisfaction (Anas et al., 2023) or purchasing decisions via Shopee Live (Fernando et al., 2023; Hsieh et al., 2024), rather than CBBE specifically in Indonesian e-commerce. Demographic factors such as education are rarely moderated in this context. This is a quantitative study with a survey design targeting active social media e-commerce consumers in Indonesia. Primary data was collected from an online questionnaire using purposive sampling, with 300 respondents who are Shopee/Tokopedia users. Multiple linear regression analysis and moderation via SPSS. SMMA has a significant positive effect on CBBE, in line with increased awareness and image in skincare (Manohar et al., 2023; Pancić et al., 2023), as well as loyalty via engagement (Bhardwaj et al., 2023; Dogra et al., 2023). Shopee Live increases purchases (Fernando et al., 2023); demographics moderate the relationship. SMMA significantly builds CBBE in Indonesian e-commerce, so companies optimize interactive strategies for long-term loyalty.